Two Cases of Neurolymphomatosis with Fatal Bilateral Vocal Cord Paralysis that were Diagnosed with (18)F-fluorodeoxyglucose Positron Emission Tomography (FDG PET)/CT - Ono, Yuichiro (Intern Med, 2017)
Neurolymphomatosis is a rare entity defined as nerve infiltration by neurotropic abnormal lymphocytes which can lead to the development of neuropathy, with typical presentations including pain, hypoesthesia, paresthesis and palsy. We herein report two cases where critical bilateral vocal cord paralysis due to neurolymphomatosis in recurrent nerves occurred in refractory Burkitt lymphoma and adult T-cell lymphoma patients. High-dose methotrexate and intrathecal chemotherapy injection for the nervous lesions were ineffective, and the patients died. Neurolymphomatosis of the recurrent nerve is an emergent and difficult complication and should be suspected when sudden onset of aphasia, hoarseness or shortness of breath is found in refractory lymphoma patients.